Association of a miRNA-137 Polymorphism with Schizophrenia in a Southern Chinese Han Population. (27th August 2014) - Ma, Guoda; Yin, Jingwen; Fu, Jiawu; Luo, Xudong; Zhou, Haihong; Tao, Hua; Cui, Lili; Li, You; Lin, Zhixiong; Zhao, Bin; Li, Zheng; Lin, Juda; et al.
Abstract : Both genome wide association study (GWAS) and biochemical studies of Caucasian populations indicate a robust association between the miR-137 genetic variant rs1625579 and schizophrenia, but inconsistent results have been reported. To assay the association between this variant and schizophrenia, we genotyped 611 schizophrenic patients from Southern Chinese Han population for the risk single nucleotide polymorphism (SNP) rs1625579 using the SNaPshot technique and compared the clinical profiles of different genotypes. Additionally, a meta-analysis was performed using the combined sample groups from five case-control publications and the present study. Both the genotype and allele distributions of the rs1625579 SNP were significantly different between patients and controls (P = 0.036 and 0.026, SNP). TT genotype carriers showed slightly lower Brief Assessment of Cognition in Schizophrenia- (BACS-) derived working memory performance than G carriers (15.58 ± 9.56 versus 19.71 ± 8.18, P = 0.045 ). In the meta-analysis, we observed a significant association between rs1625579 and schizophrenia under different genetic models (all P < 0.05 ). The results of our study and meta-analysis provide convincing evidence that rs1625579 is significantly associated with schizophrenia. Furthermore, the miR-137 polymorphism influences the working memory performance of schizophrenic patients in a Chinese Han population.